Facile synthesis of visible-responsive photocatalytic Eu-doped layered double hydroxide for selective removal of NOx pollutant - Pastor Espejo, Adrián; Chen, Chunping; De Miguel Rojas, Gustavo; Martín-Jiménez, Francisco de Paula; Cruz Yusta, Manuel; O'Hare, Dermot M.; Pavlovic Milicevic, Ivana; Sánchez-Granados, Luis (Elsevier, 2023)
Efficient nitrogen oxides (NOx) removal from the urban atmosphere is still a target for the researchers. Herein, a Zn2Al-CO3 based layered double hydroxide (LDH) was doped with increasing amounts of Eu3+ (0.01–0.04) and the photocatalytic oxidation of NOx gases was investigated. The LDHs were synthesized by a facile coprecipitation method at room temperature and ambient pressure. The successful Eu3+ substitution in the LDH layers induces a shift in the M−O bonds that modifies the electronic band structure of the doped photocatalysts. Compared to the undoped LDH, the NOx removal efficiency was enhanced by ∼ 17–25 % under UV–Vis light irradiation. Remarkably, a NOx removal efficiency of ∼ 47 % was attained by the optimally doped LDH under Visible irradiation (420 nm), surpassing raw LDH (∼ 9 %). Moreover, the Eu3+ doped LDHs retained its photocatalytic efficiency during long periods of irradiation during consecutive tests with high selectivity (>90 %). Photoluminescence studies indicated that Eu3+ was located in a non-centrosymmetric position, thereby producing structural disorder within the lattice. Eu doping promoted charge separation and a higher production of ⋅OH radicals as verified by time-resolved photoluminescence and electron paramagnetic resonance, respectively. We believe this work reports unprecedent results obtained by Eu-doping of Zn2Al-based LDHs under visible light for NOx photooxidation and serves as a new strategy to prepare functional LDHs for other photocatalytic applications
Keywords: Óxidos de nitrógeno; LDH; Photocatalyst; Nitrogen oxides; Europium; Visible Light